Analisis Resiko Kecelakaan Kerja Dengan Metode Hazard Identification Risk Assessment & Risk Control (HIRARC) : Studi Kasus: PT Madubaru PG PS Madukismo - Wati, Shinta; Andung Jati Nugroho (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
Every work environment certainly contains high potential hazards so that prevention and control efforts are needed so that work accidents do not occur. Because the production process uses machines and the work at each station has different risks of work accidents and potential sources of danger, it is necessary to analyze the Potential Hazards and Risks of Work Accidents in the Production Section of PG Madukismo using the Hazard Identification, Risk Assessment and Risk Control (HIRARC) Method. The results showed that in the work activities at PG Madukismo there was 1 work activity with extreme risk category, 34 activities with high risk category, 67 work activities with moderate risk category work activities and 15 work activities with low risk category. The control that can be done is to supervise the use of PPE such as masks, safety shoes, safety gloves, safety glasses, ear plugs, safety harnesses and helmets during the work process. Implementing engineering control by making handrails on stairs that do not have handles and making protective fences and installing toe boards and others. Administrative control is by installing warning signs and safety guards, understanding and carrying out work activities according to the SOP.